PELAKSANAAN PERJANJIAN SEWA MENYEWA ANTARA PENYEWA DENGAN PEMILIK RUMAH DI DESA KAPUR KOMPLEK GRAHA KAPUR KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - - A1012131004, YULIANA MONIKA (Jurnal Hukum Prodi Ilmu Hukum Fakultas Hukum Untan (Jurnal Mahasiswa S1 Fakultas Hukum) Universitas Tanjungpura, 2017)
As is the case in general agreement, the lease agreement that occurred at the time of the achievement of an agreement between the parties to a lease agreement. The lease agreement that was made legally must comply with Article 1320 of the Code of Civil Code so that both parties are bound to implement the agreement. The formulation of the problem in this thesis research is